Impact of genetically predicted characterization of mitochondrial DNA quantity and quality on osteoarthritis - Liu, Houpu; Cai, Bingyue; Gong, Ruicheng; Yang, Ye; Wang, Jing; Zhou, Dan; Yu, Min; Li, Yingjun (Frontiers in Genetics, 2023)
Background: Existing studies have indicated that mitochondrial dysfunction may contribute to osteoarthritis (OA) development. However, the causal association between mitochondrial DNA (mtDNA) characterization and OA has not been extensively explored. Methods: Two-sample Mendelian Randomization (MR) was performed to calculate the impact of mitochondrial function on overall OA as well as site-specific OA, with multiple analytical methods inverse variance weighted (IVW), weighted median (WM), MR-Egger and MR-robust adjusted profile score (MR-RAPS). Results: Genetically determined MtHz and mtDNA abundance were not causally associated with overall OA. In site-specific OA analyses, the causal effect of mtDNA abundance on other OA sites, including hip, knee, thumb, hand, and finger, had not been discovered. There was a suggestively protective effect of MtHz on knee OA [IVW OR= 0.632, 95% CI: 0.425-0.939, p-value= 0.023. No causal association between MtHz and other different OA phenotypes was found. Conclusions: MtHz shows potential to be a novel therapeutic target and biomarker on knee OA development. However, with MR methods, no causal role of mtDNA abundance has been detected. Additional MR analyses are warranted to explore the association between mtDNA genome traits and OA stratified by gender.